Prognostic value of biochemical response to neoadjuvant androgen deprivation before external beam radiotherapy for prostate cancer: A systematic review of the literature. (May 2016) - Zilli, Thomas; Dal Pra, Alan; Kountouri, Melpomeni; Miralbell, Raymond
Highlights: PSA response to neoadjuvant androgen deprivation predicts improved outcome. PSA decline during androgen blockade may be a marker of tumor androgen sensitivity. Therapeutic gain would be possible by individualizing treatments on PSA response. Abstract: External beam radiation therapy (EBRT) in combination with androgen deprivation therapy (ADT) is considered a standard treatment option for patients with aggressive localized and locally-advanced prostate cancer. Randomized phase III trials have provided evidence for combining EBRT to short-term ADT for intermediate-risk disease and to long-term ADT for patients harboring high-risk tumors. Even if several improvements and developments have been made in the last years in terms of radiotherapy delivery techniques, image-guided radiotherapy, and better sparing of the organs at risk the current use of ADT remains still linked to a therapeutic algorithm based on the prostate cancer risk classification as proposed by clinical trials. Emerging literature has recently shown that the biochemical response to a course of neoadjuvant ADT before EBRT, called the "prostate-specific antigen (PSA) nadir" (lowest value after treatment), may influence the long-term biochemical tumor-control outcomes of prostate cancer patients. An individualized approach adapting the duration of hormonal treatment according to the PSA response during the neoadjuvant phase, as well using new generation hormonal agents, may represent a new therapeutic strategy and a future way to improve the therapeutic ratio for prostate cancer patients. In this systematic review of the literature we explored the prognostic value of the PSA response to the neoadjuvant ADT phase and the rationale to adjust the use of ADT and EBRT in patients with intermediate- and high-risk prostate cancer based on the biochemical response to the neoadjuvant androgen ablation phase.